Bio-based lacquers from industrially processed tomato pomace for sustainable metal food packaging. (1st February 2023) - Benítez, José J.; Ramírez-Pozo, María C.; Durán-Barrantes, María M.; Heredia, Antonio; Tedeschi, Giacomo; Ceseracciu, Luca; Guzman-Puyol, Susana; Marrero-López, David; Becci, Alessandro; Amato, Alessia; Heredia-Guerrero, José A.
Abstract: Bio-based lacquers prepared from an underutilized tomato processing residue such as pomace have been investigated as sustainable alternatives to bisphenol A (BPA)-based coatings for metal food packaging. The fabrication methodology consisted of a two-step process: spray-coating of a paste of the lipid fraction of tomato pomace with a mixture ethanol:H2 O (3:1, v:v) on common metal substrates, used for food canning, such as aluminum (Al), chromium-coated tin-free steel (TFS), and electrochemically tin-plated steel (ETP), followed by the self melt-polycondensation of such lipid fraction. The polymerization reaction was conducted at 200 °C for different times (10, 20, 30, 40, 50, and 60 min) and was monitored by specular infrared spectroscopy, resulting in maximum degrees of esterification of ∼92% for Al and ∼85% for TFS and ETP substrates. The anticorrosion performance of the coatings was studied by electrochemical impedance spectroscopy at different immersion times (time intervals of 2–5 h during an overall stability test up to 170 h) in an aqueous solution of 1 wt% NaCl. The degree of polymerization and the physical properties of the coatings showed a strong dependence on the metal substrate used. In general, the best results were found for tomato pomace-based lacquers applied on aluminum, achieving higher mechanical strength (critical load of 1739 ± 198 mN for Al, 1078 ± 31 mN for ETP, and 852 ± 206 mN for TFS), hydrophobicity (water contact angle ∼95° for Al, ∼91° for ETP, and ∼88° for TFS), and improved anticorrosion performance (coating resistance of 0.7 MΩcm 2 after 170 h of immersion for Al, 0.7 MΩcm 2 after 70 h of immersion for TFS, and negligible coating resistance for ETP). In view of the technical innovation proposed in the present paper, the estimation of the environmental sustainability of the process has been considered relevant to fit the circular economy target. For this purpose, a life cycle analysis (LCA) was applied to the overall process, revealing multiple advantages for both the environment and human health. Graphical abstract: Image 1 Highlights: Tomato pomace is used to fabricate lacquers for metal packaging. A degree of esterification of ∼92% was achieved for the coating on aluminum. These bio-based lacquers show good anti-corrosion properties. A coating resistance of 0.7 MΩcm 2 after 170 h of immersion was determined for Al. The overall fabrication process is sustainable as evaluated by life cycle analysis.